PERANCANGAN EDUCATION CENTER DI JAKARTA BARAT DENGAN PENERAPAN ARSITEKTUR KONTEMPORER - Bagus Nurhasan Rahmanto; Harfa Iskandaria; Tri Endangsih (MAESTRO, 2020)
Education Center is a place or building that serves to accommodate and serve non-formal educational activities of private ownership that have teaching and learning facilities according to standards and facilities supporting learning activities by applying ideas and a contemporary (contemporary) design that is realized into a building form. Contemporary architecture in the application of Education Center buildings is based on the Hybrid Expression Style, namely the appearance of the building which is the result of a combination of contemporary elements with other architectural elements, and the Conventional and Abstract Form, which is the appearance of buildings that display conventional forms and complex forms (popular), so it's easy to understand the intent and purpose. Produce expressive building forms and have a contemporary impression.